Excellent photocatalytic degradation and antibiosis of WO3/Fe2O3 heterojunction - Jing Zhao (Materials Research Express, 2022)
The extensive light absorption, enhanced separation of photoinduced carriers and convenience of recycling are crucial for the practical application of WO _3 photocatalyst in the dye degradation and the antibiosis activity. Hence, in this work, we synthesize WO _3 /Fe _2 O _3 composite film on FTO conductive substrate through hydrothermal method. The higher degradation rate for methylene blue (MB) is achieved by WO _3 /Fe _2 O _3 composite film, and the value of C/C _0 is 0.28 which is lower than that of 0.58 for bare WO _3 with the irradiation for 4 h. Moreover, the sterilization rate of 28.99% is achieved for WO _3 -based film with the deposition of Fe _2 O _3 for 3 h. The deeper measurements indicate that the enhanced photocatalytic performances are attributed to the expand light absorption, improved transfer kinetics and separation efficiency of photoinduced carriers with the formation of heterojunction. This work establishes the effective template for WO _3 -based film with the enhanced photocatalytic prosperities for dye degradation and antibiosis.